KAJIAN LITERATUR: PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN SOSIAL DAN AKADEMIK PESERTA DIDIK - Mutiara Sri Farhani; Rinaldi Yusup (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to systematically examine the effect of the Jigsaw cooperative learning model on the development of social and academic skills of elementary school students. This study uses a Systematic Literature Review (SLR) approach with the PRISMA protocol to search, filter, and analyze relevant scientific literature from 2020 to 2025 through the Google Scholar, Researchgate, DOAJ, and SINTA databases. Of the 25 articles identified, six articles met the inclusion criteria and were analyzed further. The results of the study show that the Jigsaw model consistently encourages improvements in social skills such as collaboration, responsibility, communication, and empathy, as well as strengthening academic achievement through increased learning motivation, understanding of material, and active participation. This model provides group-based learning experiences and positive interdependence, which are effective in shaping social interactions and improving student learning achievement. Therefore, the Jigsaw learning model is considered an appropriate approach to be implemented in elementary schools in order to address the challenges of learning that require active student involvement and character building. This study provides recommendations for teachers to adapt the Jigsaw model as a contextual and applicable learning strategy.